2019
DOI: 10.2217/epi-2018-0212
|View full text |Cite
|
Sign up to set email alerts
|

Core Regulatory RNA Molecules Identified in Articular Cartilage Stem/Progenitor Cells During Osteoarthritis Progression

Abstract: Aim: To assess cartilage-derived stem/progenitor cells (CSPCs) in osteoarthritis (OA) by employing mRNA-miRNA-circRNA-lncRNA network biology approach. Methods: Differentially expressed (DE) RNAs in CSPCs from 2-/4-/8-month-old STR/Ort and CBA mice were identified to construct networks via RNA sequencing. Results: Compared with age-matched CBA mice, 4-/8-month-old STR/Ort mice had cartilage lesions and their CSPCs exhibited lower proliferative and differentiation capacity (decreased CD44 and CD90), and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…All these features were consistent with previous studies [6,25]. Moreover, our previous studies had confirmed that CPCs had the multilineage differentiation potential [26].…”
Section: Identification Of Cpcs and Cpc-derived Extracellular Vesiclessupporting
confidence: 93%
“…All these features were consistent with previous studies [6,25]. Moreover, our previous studies had confirmed that CPCs had the multilineage differentiation potential [26].…”
Section: Identification Of Cpcs and Cpc-derived Extracellular Vesiclessupporting
confidence: 93%
“…CPNE1 is a recently discovered calcium‐dependent membrane‐binding protein with a broad tissue distribution and may regulate signal transduction and membrane trafficking. Dysregulation of CPNE1 is related to various pathologies such as osteoarthritis, neuronal disorders, and tumorigenesis 9‐12,15,20 . However, its role in TNBC tumorigenesis and radioresistance is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of CPNE1 is related to various pathologies such as osteoarthritis, neuronal disorders, and tumorigenesis. [9][10][11][12]15,20 However, its role in TNBC tumorigenesis and radioresistance is not understood. In this study, CPNE1 expression was increased in BC tissues, especially in TNBC tissues, and correlated with tumor size, distant metastasis, and overall survival of patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, little effort is done aiming to investigate lncRNA expression profile in KOA. With regard to OA, a previous study elucidates that there are 7082 differentially expressed RNAs (including lncRNAs) in mice model of OA, then the OA‐related core RNAs (including lncRNAs) are identified, which are mainly enriched in signaling pathways related to inflammation and bone formation 16 . Another study reveals 2042 differentially expressed lncRNAs in OA cartilage (collected from OA patients) compared with non‐OA cartilage (collected from patients who undergo invasive procedures), including 1137 upregulated lncRNAs and 905 downregulated lncRNAs 17 .…”
Section: Discussionmentioning
confidence: 99%